Zerumbone enhances the photodynamic effect against biofilms of fluconazole-resistant Candida albicans clinical isolates - Abreu-Pereira, César Augusto [UNESP]; Gorayb-Pereira, Ana Luiza [UNESP]; Jordão, Cláudia Carolina [UNESP]; Paro, Clara Brait [UNESP]; Barbugli, Paula Aboud [UNESP]; Pavarina, Ana Claudia [UNESP] (My University, 2025)
The aim was the evaluation of Zerumbone (ZER) associated with Photodithazine® (PDZ) mediated antimicrobial photodynamic therapy (aPDT) on fluconazole-resistant (CaR) and -susceptible (CaS) Candida albicans biofilms, and well as two fluconazole-resistant clinical isolates (R70 and R14). Biofilms (48 h) were treated with ZER (256 µg/mL) for 20 min, followed by the absence or presence of the photosensitizer (PDZ; 200 mg/L) and Light Emitting Diode (LED; 600 nm; 50 Jcm2), either alone or in combination, resulting in 8 treatment groups (Control; ZER; aPDT; PDZ; LED; ZER+aPDT; ZER+PDZ; ZER+LED; n = 12). The treatments were evaluated by colony-forming unit (CFU), total and insoluble biomass, extracellular matrix components (ECM) quantification [extracellular DNA (eDNA), proteins, alkali (ASP) and water-soluble polysaccharides (WSP)], and Confocal Laser Scanning Microscopy (CLSM). Data were subjected to three-way ANOVA with Bonferroni post-test (α 5 %). The combination of ZER and aPDT promoted a greater reduction of biofilms’ components for all the strains evaluated (CaS, CaR, R14, R70). On average, ZER+aPDT group showed a 2.01 log10 (30 %) reduction in CFU counts, total biomass (30 %), insoluble biomass (33 %), and total protein (15 %). Additionally, there was a reduction in ECM components of the biofilms, such as insoluble proteins (24 %), WSP (68 %), ASP (26 %) and eDNA (60 %) compared to the control group. Images obtained through CLSM showed that the association of ZER+aPDT resulted in a higher content of dead cells. Treatment with ZER+aPDT enhanced the efficacy of photodynamic treatment on fluconazole-resistant C. albicans (including clinical isolates), representing an encouraging antifungal approach.
Keywords: Biofilms; Candida albicans; Photochemotherapy; Zerumbone